A method for preparing starch-based material with barrier properties

Through the copolymerization of polypropylene carbonate and lactide and amino acid modification of oxidation starch, the starch-based degradable material PPC-PLA-ST was prepared, which solved the problem of poor compatibility between starch and polypropylene carbonate, and achieved the Good mechanical properties, barrier properties and biocompatibility of the material.

CN116218152BActive Publication Date: 2025-02-14SHANDONG TIANMING PHARM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310254946.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-16
Publication Date
2025-02-14
Estimated Expiration
2043-03-16

AI Technical Summary

Technical Problem

In the prior art, starch has poor compatibility with polypropylene carbonate, resulting in poor mechanical properties, and it is difficult to maintain excellent barrier properties of polycarbonate.

Method used

Polyester PPC-PLA was prepared by melt copolymerization of polypropylene carbonate polyol and lactide. The oxidized starch was grouped with amino acids to form AA-ST, and then the two were refined and extruded to obtain starch The base degradable material PPC-PLA-ST.

Benefits of technology

The tensile and impact resistance of starch is improved, the mechanical strength and biocompatibility of the material are enhanced, and the cross-linking degree between starch and polyester is improved through the bicarboxyl group and amino group, achieving good barrier properties and Degradation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116218152B_ABST
    Figure CN116218152B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a starch-based material with barrier properties. The present invention prepares polyester PPC-PLA by melt copolymerization of polypropylene carbonate polyol and lactide, performs group modification on oxidized starch by amino acids to obtain AA-ST, and then performs banburying and extrusion to obtain starch-based degradable material PPC-PLA-ST. The addition of PPC not only improves the tensile strength and impact resistance of starch, but also enables the material to have certain barrier properties. The addition of polylactide enhances the mechanical strength of the material. The addition of amino acids enables the material to have good biocompatibility, and the crosslinking degree between starch and polyester is increased by dicarboxyl and amino groups. Therefore, the prepared product has good barrier properties, good mechanical properties and biocompatibility, and can be completely degraded, and can be used in food film packaging, ground film and pharmaceutical industries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bio-based polymer materials, and in particular relates to a method for preparing a starch-based material with barrier properties. Background Art

[0002] Since the invention of plastic in the 20th century, it has been widely used due to its good performance. Among them, plastic packaging materials have developed the fastest. Plastic packaging materials account for 41% of domestic waste, and this kind of waste is "permanent" and non-degradable. Therefore, the development of naturally degradable plastic products to replace ordinary plastics is a current research hotspot. Starch is a natural degradable polymer material. It can be broken into monosaccharides such as glucose and other small molecular compounds under the action of microorganisms, and finally metabolized into water and carbon dioxide. It is renewable and low-priced. It is a strong substitute for non-degradable petroleum-based materials. At this stage, starch can only have thermoplastic properties by adding small molecule plasticizers or compatibilizers, but with the migration of small molecule substances, its safety cannot be guaranteed.

[0003] Carbon dioxide copolymer is a general term for polymers generated by the copolymerization of carbon dioxide and other copolymerizable monomers. Its synthesis began with the work published by Japanese scientist Shohei Inoue in 1696. At present, the polymers generated by the copolymerization of carbon dioxide and epoxides are more studied. Carbon dioxide and propylene oxide are polymerized under the action of catalysts to generate polypropylene carbonate (PPC). As a new type of aliphatic polyester, PPC has good degradation and barrier properties, and is transparent and non-toxic. Therefore, it has good prospects in food packaging, medical materials, and engineering plastics. It is generated by the copolymerization of carbon dioxide and propylene oxide under the action of catalysts. On the one hand, carbon dioxide can be used to reduce the greenhouse effect, and on the other hand, it reduces the dependence of plastics on petroleum resources. However, PPC has a low glass transition temperature, low tensile strength, and poor thermal stability.

[0004] Patent CN111607209A discloses a high-performance polypropylene carbonate composition and a preparation method thereof, which is prepared by blending clay, starch composite and polypropylene carbonate resin, which can improve its thermal stability and is environmentally friendly, but also has the disadvantage that starch and polypropylene carbonate have poor compatibility, which deteriorates its mechanical properties.

[0005] Therefore, it is necessary to provide a material that can maintain the excellent barrier properties of polycarbonate while also having certain mechanical properties and a low price. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides a method for preparing a starch-based material with barrier properties. The present invention prepares polyester PPC-PLA by melt copolymerization of polypropylene carbonate polyol and lactide, and groups the oxidized starch by amino acids to obtain AA-ST, and then the two are kneaded and extruded to obtain starch-based degradable material PPC-PLA-ST. The addition of PPC not only improves the tensile strength and impact resistance of starch, but also makes the material have certain barrier properties. The addition of polylactide enhances the mechanical strength of the material. The addition of amino acids makes the material have good biocompatibility, and the crosslinking degree between starch and polyester is increased by dicarboxyl and amino groups. Therefore, the prepared product has good barrier properties, good mechanical properties and biocompatibility, and can be completely degraded, and can be used in food film packaging, ground film and pharmaceutical industries.

[0007] The technical solution of the present invention is: a method for preparing a starch-based material with barrier properties, characterized in that it comprises the following steps:

[0008] 1) using polypropylene carbonate polyol (PPC) and lactide (LA) as raw materials, using a catalyst to carry out copolymerization reaction at a temperature of 100-140° C. and normal pressure for 12-48 hours to obtain solid polyester PPC-PLA, and then crushing it with a crusher to obtain PPC-PLA particles;

[0009] 2) dissolving oxidized starch and amino acid in water, heating to 40-80° C. under stirring to obtain AA-ST, drying and removing water, and grinding to obtain AA-ST powder with a particle size of >100 mesh;

[0010] 3) The AA-ST powder and the PPC-PLA particles are mixed and extruded in a screw extruder to obtain the starch-based biodegradable material PPC-PLA-ST.

[0011] The schematic diagram of the preparation of the above steps 1) to 3) and the product structure is as follows Figure 1 As shown. The method of cross-linking with amino acids enhances the connectivity between starch and polyester, increases their compatibility, and thus greatly enhances the mechanical properties of the material.

[0012] Preferably, the polypropylene carbonate polyol in step 1) is one of polypropylene carbonate diol (PPC), polypropylene carbonate triol (3-PPC), and polypropylene carbonate tetraol (4-PPC), more preferably PPC; its molecular weight is 500 to 10000 g / mol, and the more preferred molecular weight of the polycarbonate polyol is 3000 to 8000 g / mol.

[0013] Preferably, in step 1), the molar ratio of polypropylene carbonate polyol to lactide is 1:10-100, and more preferably the molar ratio of polycarbonate polyol to lactide is 1:30-60.

[0014] Preferably, the catalyst in step 1) is a tin compound, more preferably stannous octoate, and the amount added is 0.01%-0.3wt% of the total mass of the raw materials in step 1).

[0015] Preferably, in step 2), the oxidation degree of the starch is 10-60%; and the amino acid is one or both of glutamic acid and aspartic acid.

[0016] Preferably, in step 2), the mass ratio of oxidized starch to amino acid is 100:10-50.

[0017] Preferably, the reaction time of step 2) is 0.5-3h.

[0018] Preferably, in step 3), the mass ratio of AA-ST to PPC-PLA is 100:80-200.

[0019] Preferably, the banburying conditions in step 3) are: the banburying temperature during screw extrusion is 140° C.-200° C., the banburying speed is 20-80 rpm, and the banburying time is 3-10 min.

[0020] The barrier starch-based material prepared by the above method is characterized in that the mass content of starch in the material PPC-PLA-ST is 30-50%.

[0021] The barrier starch-based material prepared by the above method can be completely degraded (degradation time ≤ 24 days), with a breaking strength of > 27MPa, a breaking elongation of > 121%, and a water vapor permeability of < 134g / m 2 / 24h, oxygen transmission rate <185cm 3 / m 2 / d / atm, so it has broad application prospects in packaging, agriculture, medical and other fields.

[0022] The present invention has the following beneficial effects:

[0023] 1. In the product of the present invention, the addition of PPC not only improves the tensile properties and impact resistance of starch, but also enables the material to have certain barrier properties. The addition of polylactide enhances the mechanical strength of the material, so that the product has better mechanical properties. The addition of amino acids enables the material to have good biocompatibility (no other small molecule plasticizers, coupling agents, or dispersants need to be added to ensure good compatibility). The crosslinking degree between starch and polyester is increased by dicarboxyl groups and amino groups, thereby increasing the starch content and reducing costs.

[0024] 2. No small molecule additives are used in the material preparation process of the present invention, and the raw materials used are all completely degradable. The product has certain barrier properties, so it can be used to make various tableware, packaging materials that directly contact food, medical materials and agricultural films, etc. The product is green and degradable, and the degradation products are harmless to the human body.

[0025] 3. Compared with the traditional method, the preparation method of the present invention has a simple process, does not require organic solvent treatment, and does not require other small molecule additives. The starch content is high and the source is wide, making the price low and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the preparation of the starch-based material with barrier properties and the product structure of the present invention;

[0027] Figure 2 This is a picture of the membrane PPC-PLA-ST-1 prepared in Example 1. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.

[0030] The present invention will be further explained and illustrated below in conjunction with the embodiments.

[0031] Example 1

[0032] 300g of PPC (M n =6000g / mol) and 300g L-lactide were placed in a flask, 0.6g of stannous octoate was added, the temperature was raised to 140°C, and the mixture was reacted for 24h under magnetic stirring to obtain a milky white polyester PPC-PLA-1, which was then crushed by a pulverizer to obtain PPC-PLA-1 particles;

[0033] Dissolve 400g of oxidized starch (oxidation degree 50%) and 80g of aspartic acid in 1000ml of deionized water, stir evenly, heat to 60°C, stir at 150rmp, react for 2h, freeze-dry, and grind to obtain AA-ST-1 powder (110 mesh);

[0034] 400g AA-ST-1 powder and 600g PPC-PLA-1 granules were added into a screw extruder, and the mixture was kneaded for 5 minutes at a temperature of 150°C and a rotation speed of 60 rpm. The product was extruded, granulated by air cooling, and blown into film in a blow molding machine at 160°C to obtain a PPC-PLA-ST-1 film. The product picture is shown in the figure. Figure 2 As shown, a dumbbell-shaped specimen M1 (thickness 1 mm) was made using a rubber pneumatic slicer.

[0035] Example 2

[0036] 500g of PPC (M n =6000g / mol) and 300g L-lactide were placed in a flask, 0.8g of stannous octoate was added, the temperature was raised to 150°C, and the mixture was reacted for 20h under magnetic stirring to obtain a milky white polyester PPC-PLA-2, which was then crushed by a pulverizer to obtain PPC-PLA-2 particles;

[0037] Dissolve 400g of oxidized starch (oxidation degree 50%) and 80g of aspartic acid in 1000ml of deionized water, stir evenly, heat to 60°C, stir at 150rmp, react for 2h, freeze-dry, and grind to obtain AA-ST-2 powder (105 mesh);

[0038] 400 g of AA-ST-2 powder and 600 g of PPC-PLA-2 granules were added to a screw extruder, and the mixture was kneaded for 7 min at a temperature of 150 ° C and a rotation speed of 55 rpm. The product was extruded, granulated by air cooling, and blown into a film in a blow molding machine at 160 ° C to finally obtain a PPC-PLA-ST-2 film, which was then formed into dumbbell-shaped specimens M2 (1 mm thick) using a rubber pneumatic slicer.

[0039] Example 3

[0040] 300g of 3-PPC (M n =6000g / mol) and 300g L-lactide were placed in a flask, 0.6g of stannous octoate was added, the temperature was raised to 130°C, and the mixture was reacted for 28h under magnetic stirring to obtain a milky white polyester PPC-PLA-3, which was then crushed by a pulverizer to obtain PPC-PLA-3 particles;

[0041] Dissolve 400g of oxidized starch (oxidation degree 50%) and 80g of aspartic acid in 1000ml of deionized water, stir evenly, heat to 60°C, stir at 150rmp, react for 2h, freeze-dry, and grind to obtain AA-ST-3 powder (120 mesh);

[0042] 400 g of AA-ST-3 powder and 600 g of PPC-PLA-3 were added to a screw extruder, and the mixture was kneaded for 6 min at a temperature of 160 ° C and a rotation speed of 60 rpm. The product was extruded, granulated by air cooling, and blown into a film in a blow molding machine at 160 ° C to finally obtain a PPC-PLA-ST-3 film, which was then formed into dumbbell-shaped specimens M3 (thickness of 1 mm) using a rubber pneumatic slicer.

[0043] Example 4

[0044] 300g of PPC (M n =6000g / mol) and 300g L-lactide were placed in a flask, 0.6g of stannous octoate was added, the temperature was raised to 140°C, and the mixture was reacted for 24h under magnetic stirring to obtain a milky white polyester PPC-PLA-4, which was then crushed by a pulverizer to obtain PPC-PLA-4 particles;

[0045] Dissolve 600g of oxidized starch (oxidation degree 50%) and 120g of aspartic acid in 1500ml of deionized water, stir evenly, heat to 70°C, stir at 180rmp, react for 3h, freeze-dry, and grind to obtain AA-ST-4 powder (125 mesh);

[0046] 600g AA-ST-4 powder and 600g PPC-PLA-4 were added to a screw extruder, and the mixture was kneaded for 5 minutes at a temperature of 140°C and a rotation speed of 50 rpm. The product was extruded, granulated by air cooling, and blown into a film in a blow molding machine at 160°C to finally obtain a PPC-PLA-ST-4 film, which was then formed into dumbbell-shaped strips M4 (1 mm thick) using a rubber pneumatic slicer.

[0047] Example 5

[0048] 300g of PPC (M n =4000g / mol) and 300g L-lactide were placed in a flask, 0.6g of stannous octoate was added, the temperature was raised to 140°C, and the mixture was reacted for 28h under magnetic stirring to obtain a milky white polyester PPC-PLA-5, which was then crushed by a pulverizer to obtain PPC-PLA-5 particles;

[0049] Dissolve 400g of oxidized starch (oxidation degree 50%) and 80g of aspartic acid in 1000ml of deionized water, stir evenly, heat to 50°C, stir at 160rmp, react for 2.5h, freeze-dry, and grind to obtain AA-ST-5 powder (105 mesh);

[0050] 400 g AA-ST-5 powder and 600 g PPC-PLA-5 were added to a screw extruder, and the mixture was kneaded for 7 min at a temperature of 150 ° C and a rotation speed of 60 rpm. The product was extruded, granulated by air cooling, and blown into a film in a blow molding machine at 160 ° C to finally obtain a PPC-PLA-ST-5 film, which was then formed into dumbbell-shaped specimens M5 (thickness of 1 mm) using a rubber pneumatic slicer.

[0051] Example 6

[0052] 300g of PPC (M n =6000g / mol) and 500g L-lactide were placed in a flask, 0.8g of stannous octoate was added, the temperature was raised to 140°C, and the mixture was reacted for 30h under magnetic stirring to obtain a milky white polyester PPC-PLA-6, which was then crushed by a pulverizer to obtain PPC-PLA-6 particles;

[0053] Dissolve 400 g of oxidized starch (oxidation degree 50%) and 80 g of aspartic acid in 1000 ml of deionized water, stir evenly, heat to 60° C., stir at 150 rpm, react for 2 h, freeze-dry, and grind to obtain AA-ST-6 powder (115 mesh);

[0054] 400 g AA-ST-6 and 600 g PPC-PLA-6 were added to a screw extruder, and the mixture was kneaded for 7 min at a temperature of 160 ° C and a rotation speed of 60 rpm. The product was extruded, granulated by air cooling, and blown into a film in a blow molding machine at 160 ° C to finally obtain a PPC-PLA-ST-6 film, which was then formed into dumbbell-shaped specimens M6 (thickness of 1 mm) using a rubber pneumatic slicer.

[0055] Example 7

[0056] 300g of PPC (M n =6000g / mol) and 300g L-lactide were placed in a flask, 0.6g of stannous octoate was added, the temperature was raised to 140°C, and the mixture was reacted for 24h under magnetic stirring to obtain a milky white polyester PPC-PLA-7, which was then crushed by a pulverizer to obtain PPC-PLA-7 particles;

[0057] Dissolve 400g of oxidized starch (oxidation degree 40%) and 120g of glutamic acid in 1000ml of deionized water, stir evenly, heat to 70°C, stir at 200rmp, react for 3h, freeze-dry, and grind to obtain AA-ST-7 powder (120 mesh);

[0058] 400 g of AA-ST-7 powder and 600 g of PPC-PLA-7 granules were added to a screw extruder, and the mixture was kneaded for 5 min at a temperature of 150 ° C and a rotation speed of 60 rpm. The product was extruded, granulated by air cooling, and blown into a film in a blow molding machine at 160 ° C to finally obtain a PPC-PLA-ST-1 film, which was then formed into dumbbell-shaped specimens M7 (thickness 1 mm) using a rubber pneumatic slicer.

[0059] Test example:

[0060] Mechanical properties: The HY939C computerized single-column tensile testing machine of Guangdong Dongguan Hengyu Instrument Co., Ltd. was used to measure the breaking strength and elongation of the film at a stretching rate of 50 mm / min. The water vapor permeability of the film was measured using the water vapor permeability C390 (infrared method) of Jinan Languang Electromechanical Technology Co., Ltd.; the oxygen permeability of the film was measured using the G2 / 131X differential pressure gas permeability tester of Jinan Languang Electromechanical Technology Co., Ltd.

[0061] Degradation performance: The degradation performance of the material is evaluated by testing its tensile strength at different stages. The membrane material is immersed in 37°C saline and measured for one day. When the tensile strength is zero, the degradation is considered complete.

[0062] Table 1 Properties of samples prepared in Examples 1 to 6

[0063]

[0064] The test results are shown in Table 1. From the performance of the film samples in Table 1, it can be seen that the film material not only has good breaking strength, breaking elongation and barrier properties (low water vapor and oxygen permeability), but also has good degradation performance; the increase of PPC content (M2) will reduce its mechanical strength, but enhance the barrier performance; with the increase of PPC functionality (M3) or the decrease of molecular weight (M5), the mechanical strength of the material can also be increased; the increase of PLA content (M6) will reduce the flexibility of the material, but enhance the mechanical strength; the increase of amino acid content (M7) also increases the crosslinking degree between starch and polyester, thereby improving the mechanical properties; starch content (M4) mainly affects the degradation time of the material. By adjusting the ratio, materials suitable for different directions can be obtained.

Claims

1. A method for preparing a starch-based material having barrier properties, characterized in that: The following steps are involved: 1) Using polypropylene carbonate polyol and lactide as raw materials, using a catalyst to carry out copolymerization reaction at a temperature of 100-140° C. and normal pressure for 12-48 hours to obtain solid polyester PPC-PLA, and then crushing to obtain PPC-PLA particles; 2) dissolving oxidized starch and amino acid in water, heating to 40-80°C under stirring to obtain AA-ST, drying and removing water, and grinding to obtain AA-ST powder with a particle size of >100 mesh; 3) The AA-ST powder and the PPC-PLA granules are mixed and extruded in a screw extruder to obtain the barrier starch-based material PPC-PLA-ST.

2. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 1), the polypropylene carbonate polyol is one of polypropylene carbonate diol, polypropylene carbonate triol and polypropylene carbonate tetraol; and its molecular weight Mn is 500-10000 g / mol.

3. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 1), the molar ratio of polypropylene carbonate polyol to lactide is 1:10-100.

4. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 1), the catalyst is a tin compound, and the amount added is 0.01%-0.3 wt % of the total mass of the raw materials in step 1).

5. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 2), the oxidation degree of the starch is 10-60%; and the amino acids are glutamic acid and / or aspartic acid.

6. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 2), the mass ratio of oxidized starch to amino acid is 100:10-50.

7. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 3), the banburying conditions are: the banburying temperature during screw extrusion is 140° C.-200° C., the banburying speed is 20-80 rpm, and the banburying time is 3-10 min.

8. The method for preparing a starch-based material with barrier properties as claimed in claim 1, characterized in that: In the step 3), the mass ratio of AA-ST to PPC-PLA is 100:80-200.

9. The barrier starch-based material prepared by the method according to any one of claims 1 to 8, characterized in that: The mass percentage of the starch in the barrier starch-based material PPC-PLA-ST is 30-50%.

10. The barrier starch-based material according to claim 9, characterized in that: It can be completely degraded, the degradation time is ≤24 days, the breaking strength is >27MPa, the breaking elongation is >121%, and the water vapor transmission rate is <134g / m 2 / 24h, oxygen transmission rate <185cm 3 / m 2 / d / atm.

Citation Information

Patent Citations

  • Poly (alkene carbonate) diol-polylactic acid segmented copolymer and preparation method thereof

    CN102241813A

  • Biodegradable resin and preparation method thereof

    CN103087487A